Programma: 5-8 december Ensemble Arlet Bon; 12-15 december Antonov Ben Lebanon; 19-22 december The Deaf School; 26-29 december Friends Roadshow - Flaum, Mick,
Programma: 5-8 december Ensemble Arlet Bon; 12-15 december Antonov Ben Lebanon; 19-22 december The Deaf School; 26-29 december Friends Roadshow.